Titanium gypsum-based baking-free brick and preparation method thereof
Through the combination of titanium gypsum, cement and other materials and the blending and modification of composite fiber powder, high-performance titanium gypsum-based flammable bricks were prepared, solving the problems of high energy consumption, high cost and performance in the existing titanium gypsum-free brick preparation methods, and achieving efficient resource utilization and performance improvement of titanium gypsum.
Patent Information
- Application Number
- CN202510044330.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-11
- Publication Date
- 2025-04-15
AI Technical Summary
The existing preparation method for titanium gypsum fire-free blocks has problems such as high energy consumption, high cost and performance that need to be improved.
Titanium gypsum, cement, gravel aggregate, slag powder, calcium carbide slag and other materials are used, and curing and adding curing agent and waterproofing agent are made by mixing and mixing of static bricks. High-performance titanium gypsum-based fire-free bricks are prepared by mixing and modification of composite fiber powder.
It realizes efficient resource utilization of titanium gypsum, improves the compressive strength of the block, reduces the water absorption rate, increases the softening coefficient, and reduces production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic non-metallic materials and solid waste resource utilization, and more specifically, the invention relates to a titanium gypsum-based unfired brick and a preparation method thereof. Background Art
[0002] At present, the annual output of titanium gypsum in my country exceeds 10 million tons. However, due to its high water content, high viscosity and high iron impurities, it has not been effectively utilized and has been stored in large quantities. At present, the effective ways to utilize titanium gypsum as a resource are mainly concentrated in the field of building materials, including cement retarder, preparation of unfired blocks, making roadbed and embankment materials, preparation of semi-hydrated gypsum, etc. Among them, the preparation of unfired blocks with titanium gypsum has attracted widespread attention due to its low cost and energy consumption, economic benefits and environmental benefits.
[0003] At present, titanium gypsum unfired blocks are mainly prepared in two ways. One is to mix titanium gypsum with auxiliary materials after calcination and frying to prepare unfired blocks. For example, in the patent with application number 201210205306.1, titanium gypsum calcined at 160-180°C is mixed with building gypsum, activator, and water reducer for casting to prepare unfired blocks. This method has the disadvantages of high energy consumption and high cost. Another method is to directly mix titanium gypsum with cement and other materials and directly press it into shape, and obtain unfired blocks after curing. For example, in the patent with application number 202210747558.0, titanium gypsum is mixed with cement, mud, gypsum, curing agent, and alkali-eliminating agent, and then pressed into shape to prepare bricks, and titanium gypsum unfired blocks are obtained after curing. However, the titanium gypsum unfired blocks prepared by direct pressing and molding reported at present still have the problems of high cost and performance to be improved. Summary of the invention
[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0005] In order to achieve these purposes and other advantages according to the present invention, a titanium gypsum-based unfired brick is provided, comprising: by mass percentage, 65.0-85.0%, cement 5.0-25.0%, sand and gravel aggregate 0-30.0%, slag powder 0-15%, and carbide slag 0-3%.
[0006] Preferably, the cement is ordinary Portland cement.
[0007] Preferably, the cement is 42.5R ordinary silicate; The slag powder is S95 grade slag powder; The carbide slag is mainly composed of calcium hydroxide, and the content of calcium hydroxide is greater than 90%.
[0008] Preferably, the composition further comprises 0.05% to 0.5% by mass of a curing agent and 0.05% to 0.5% by mass of a waterproofing agent.
[0009] Preferably, the titanium gypsum particles are filtered through a plate and frame filter press to obtain a titanium gypsum filter cake, and then the titanium gypsum filter cake is hammer-crushed and dispersed to prepare the titanium gypsum filter cake.
[0010] Preferably, the curing agent is a high molecular polymer, including one or more of polyacrylamide, polyvinyl acetate, polyurethane, polyvinyl alcohol, aniline formaldehyde resin, phenolic resin, furan resin, polyamide resin, and polyester resin.
[0011] Preferably, the waterproofing agent is a silicone waterproofing agent.
[0012] A method for preparing titanium gypsum-based unfired bricks comprises the following steps: Step 1, mixing titanium gypsum particles, cement, sand and gravel aggregate, slag powder and carbide slag to obtain a mixture; Step 2: Add the curing agent and waterproofing agent into water and stir to obtain a mixed solution; Step 3: After the mixture and the mixed liquid are stirred and mixed evenly, they are placed in a mold and pressed in two directions by a static brick-making machine to obtain a brick blank; after curing the brick blank for 7 to 28 days, titanium gypsum-based unfired bricks can be obtained.
[0013] Preferably, in step 2, the amount of water used is 10% to 30% of the mass of the mixed material.
[0014] Preferably, the prepared titanium gypsum unfired brick is tested according to GB / T17431-1998, and its compressive strength is between 5.00 and 30.00 MPa, the water absorption rate is less than 10%, and the softening coefficient is above 0.8.
[0015] In order to improve the compressive strength of titanium gypsum-based unfired bricks, reduce water absorption and increase softening coefficient, titanium gypsum is filtered through a plate-frame filter press to obtain a titanium gypsum filter cake, and then the titanium gypsum filter cake is hammer-crushed and broken up, and then blended and modified with composite fiber powder, wherein the preparation method of the composite fiber powder includes: S1. Alumina fiber and glass fiber with a breaking strength of 55-120 cN / dtex are put into a ball mill, wherein the mass ratio of alumina fiber to glass fiber is 1-3:4-7; zirconium oxide is used as a grinding ball, and the mass of the grinding ball is 2-5 times the total mass of the alumina fiber and the glass fiber; anhydrous ethanol is used as a ball milling medium, and the amount of anhydrous ethanol is 1-1.5 times the total volume of the alumina fiber and the glass fiber; polyethylene glycol of 2-10% of the mass of the glass fiber is added as a ball milling lubricant, the ball milling speed is 500-1200 rpm, and the ball milling time is 6-12 hours; after the ball milling is completed, the solid-liquid separation is performed, and the solid material is washed with deionized water and then dried to obtain a composite fiber powder; S2. Disperse the composite fiber powder and titanium gypsum particles in deionized water to obtain a mixed suspension, wherein the amount ratio of the composite fiber powder, titanium gypsum particles and deionized water is 1-10g:20-50g:400-600mL; raise the temperature of the mixed suspension to 40-60°C, add isopropyl triisostearoyl titanate, wherein isopropyl triisostearoyl titanate accounts for 1-5% of the mass of the titanium gypsum particles; stir at 200-600rpm for 1-3h, and let stand for 12-48h; after standing, filter, wash and dry to obtain titanium gypsum particles modified by the composite fiber powder blend.
[0016] The present invention includes at least the following beneficial effects: the present invention mainly adopts titanium gypsum to prepare a high-performance unfired building block, thereby realizing the resource utilization of titanium gypsum. In the titanium gypsum-based unfired brick material system, the consolidation formed by the cement hydration product plays an important supporting role. The main component of titanium gypsum is calcium sulfate dihydrate, which can stimulate the activity of slag together with cement and carbide slag, and synergistically promote the performance of the building block. The iron hydroxide in titanium gypsum has strong stability and will exist as a filler in the building block without causing harm to the performance of the building block. In addition, the excessive alkaline substances in titanium gypsum can also promote the hydration and hardening of the building block without adding an alkali-eliminating agent. Slag and carbide slag in the material system as a large amount of solid waste can significantly replace the amount of cement, which not only saves costs, but also reduces carbon dioxide emissions and energy consumption in the cement production process. In fact, highly active solid wastes such as lithium slag, fly ash, yellow phosphorus slag and silica fume can also play a role similar to slag. Sand and gravel aggregates can reduce production costs and improve construction efficiency. In addition, the polymer curing agent and silicone waterproofing agent used in this technology can form an organic molecular layer on the microscopic interface of the solidified body, which plays a role in consolidation and water repellency, thereby significantly improving the waterproof performance of the block. Finally, the titanium gypsum does not need to be dried and dehydrated during the preparation of the block, further reducing the production cost in the resource recovery process.
[0017] The present invention simultaneously utilizes alumina fiber and glass fiber to obtain composite fiber powder after ball milling, and uses the composite fiber powder to blend and modify titanium gypsum particles through dispersion and coupling. Titanium gypsum particles introduced with alumina fiber and glass fiber are used as the main raw material. The prepared titanium gypsum-based unfired bricks have more excellent compressive strength, lower water absorption and higher softening coefficient, and the performance of the titanium gypsum-based unfired bricks is further improved.
[0018] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION
[0019] The present invention is described in further detail below so that those skilled in the art can implement it according to the description.
[0020] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof. Example 1 This embodiment provides a method for preparing titanium gypsum-based unfired bricks, comprising the following steps: Step 1, 3250g of titanium gypsum particles, 700g of cement, 750g of sand and gravel aggregate, 250g of slag and 50g of carbide slag are stirred and mixed to obtain a mixture; wherein the titanium gypsum particles are obtained by neutralizing titanium dioxide waste liquid, filtering the filter cake obtained by plate and frame pressing, and dispersing it through a hammer crusher and a disperser, and the main components are calcium sulfate dihydrate and ferric hydroxide, and it also contains a certain amount of water; the cement is 42.5R ordinary Portland cement, the slag is S95 grade slag powder, and the calcium hydroxide content in the carbide slag is greater than 90%; Step 2: Add 25 g of high molecular polymer curing agent polyacrylamide and 50 g of silicone waterproofing agent into 875 mL of water, and stir to obtain a mixed solution; Step 3: Stir the mixture and the mixed liquid until evenly mixed and place them in a mold. Use a static pressing brick machine to make a 240mm×115mm×53mm rectangular green body under a bidirectional pressure of 20 kN to obtain a brick. Use a standard constant temperature and humidity curing box to cure the brick for 28 days to obtain a titanium gypsum-based unfired brick.
[0021] Example 2 This embodiment provides a method for preparing titanium gypsum-based unfired bricks, comprising the following steps: Step 1, 3250g of titanium gypsum particles, 550g of cement, 750g of sand and gravel aggregate, 400g of slag and 50g of carbide slag are stirred and mixed to obtain a mixture; wherein the titanium gypsum particles are obtained by neutralizing titanium dioxide waste liquid, filtering the filter cake obtained by plate and frame pressing, and dispersing it through a hammer crusher and a disperser, and the main components are calcium sulfate dihydrate and ferric hydroxide, and it also contains a certain amount of water; the cement is 42.5R ordinary Portland cement, the slag is S95 grade slag powder, and the calcium hydroxide content in the carbide slag is greater than 90%; Step 2: Add 25 g of high molecular polymer curing agent polyacrylamide and 50 g of silicone waterproofing agent into 875 mL of water, and stir to obtain a mixed solution; Step 3: Stir the mixture and the mixed liquid until evenly mixed and place them in a mold. Use a static pressing brick machine to make a 240mm×115mm×53mm rectangular green body under a bidirectional pressure of 20 kN to obtain a brick. Use a standard constant temperature and humidity curing box to cure the brick for 28 days to obtain a titanium gypsum-based unfired brick.
[0022] Example 3 This embodiment provides a method for preparing titanium gypsum-based unfired bricks, comprising the following steps: Step 1, 3250g of titanium gypsum particles, 400g of cement, 750g of sand and gravel aggregate, 550g of slag and 50g of carbide slag are stirred and mixed to obtain a mixture; wherein the titanium gypsum particles are obtained by neutralizing titanium dioxide waste liquid, filtering the filter cake obtained by plate and frame pressing, and dispersing it through a hammer crusher and a disperser, and the main components are calcium sulfate dihydrate and ferric hydroxide, and it also contains a certain amount of water; the cement is 42.5R ordinary Portland cement, the slag is S95 grade slag powder, and the calcium hydroxide content in the carbide slag is greater than 90%; Step 2: Add 25 g of high molecular polymer curing agent polyacrylamide and 50 g of silicone waterproofing agent into 875 mL of water, and stir to obtain a mixed solution; Step 3: Stir the mixture and the mixed liquid until evenly mixed and place them in a mold. Use a static pressing brick machine to make a 240mm×115mm×53mm rectangular green body under a bidirectional pressure of 20 kN to obtain a brick. Use a standard constant temperature and humidity curing box to cure the brick for 28 days to obtain a titanium gypsum-based unfired brick.
[0023] Example 4 This embodiment provides a method for preparing titanium gypsum-based unfired bricks, comprising the following steps: Step 1, 3250g of titanium gypsum particles, 400g of cement, 750g of sand and gravel aggregate, 700g of slag and 50g of carbide slag are stirred and mixed to obtain a mixture; wherein the titanium gypsum particles are obtained by neutralizing titanium dioxide waste liquid, filtering the filter cake obtained by plate and frame pressing, and dispersing it through a hammer crusher and a disperser, and the main components are calcium sulfate dihydrate and ferric hydroxide, and it also contains a certain amount of water; the cement is 42.5R ordinary Portland cement, the slag is S95 grade slag powder, and the calcium hydroxide content in the carbide slag is greater than 90%; Step 2: Add 25 g of high molecular polymer curing agent polyacrylamide and 50 g of silicone waterproofing agent into 875 mL of water, and stir to obtain a mixed solution; Step 3: Stir the mixture and the mixed liquid until evenly mixed and place them in a mold. Use a static pressing brick machine to make a 240mm×115mm×53mm rectangular green body under a bidirectional pressure of 20 kN to obtain a brick. Use a standard constant temperature and humidity curing box to cure the brick for 28 days to obtain a titanium gypsum-based unfired brick.
[0024] Example 5 This embodiment provides a method for preparing titanium gypsum-based unfired bricks, which is different from Example 3 in that 3250 g of titanium gypsum particles are replaced with titanium gypsum particles modified by composite fiber powder blending, wherein the preparation method of titanium gypsum particles modified by composite fiber powder blending is: S1. Put 1000g of alumina fiber and 4000g of glass fiber with a breaking strength of 60cN / dtex into a ball mill; use zirconium oxide as grinding balls with a mass of 20000g; use anhydrous ethanol as the ball milling medium, and the amount of anhydrous ethanol is 1.5 times the total volume of the alumina fiber and the glass fiber; add 400g of polyethylene glycol as a ball milling lubricant, the ball milling speed is 500rpm, and the ball milling time is 6h; after the ball milling is completed, the solid-liquid separation is carried out, the solid material is washed with deionized water and then dried to obtain a composite fiber powder; S2. Disperse 1000 g of composite fiber powder and 4000 g of titanium gypsum particles in 50000 mL of deionized water to obtain a mixed suspension; raise the temperature of the mixed suspension to 60°C, add 100 g of isopropyl triisostearyl titanate; stir at 200 rpm for 3 hours, and let stand for 24 hours; after standing, filter, wash and dry to obtain composite fiber powder blended and modified titanium gypsum particles.
[0025] The methods and process parameters of the remaining steps of this embodiment are the same as those of Embodiment 3.
[0026] Example 6 This embodiment provides a method for preparing titanium gypsum-based unfired bricks, which is different from Example 3 in that 3250 g of titanium gypsum particles are replaced with titanium gypsum particles modified by composite fiber powder blending, wherein the preparation method of titanium gypsum particles modified by composite fiber powder blending is: S1. Put 3000g of alumina fiber and 7000g of glass fiber with a breaking strength of 120cN / dtex into a ball mill; use zirconium oxide as grinding balls with a mass of 25000g; use anhydrous ethanol as the ball milling medium, and the amount of anhydrous ethanol used is 1.5 times the total volume of the alumina fiber and the glass fiber; add 600g of polyethylene glycol as a ball milling lubricant, the ball milling speed is 600rpm, and the ball milling time is 10h; after the ball milling is completed, the solid and liquid are separated, the solid material is washed with deionized water and then dried to obtain a composite fiber powder; S2. Disperse 1000 g of composite fiber powder and 4000 g of titanium gypsum particles in 50000 mL of deionized water to obtain a mixed suspension; raise the temperature of the mixed suspension to 60°C, add 150 g of isopropyl triisostearyl titanate; stir at 400 rpm for 2 hours, and let stand for 24 hours; after standing, filter, wash and dry to obtain composite fiber powder blended and modified titanium gypsum particles.
[0027] The methods and process parameters of the remaining steps of this embodiment are the same as those of Embodiment 3.
[0028] Comparative Example 1 This comparative example provides a method for preparing titanium gypsum-based unfired bricks. The difference from Example 3 is that 3250 g of titanium gypsum particles are replaced with a mixture of equal masses of alumina fiber powder, glass fiber powder, and titanium gypsum particles, that is, 130 g of alumina fiber, 520 g of glass fiber powder, and 2600 g of titanium gypsum particles are mixed, and the mixed mixture is used to prepare titanium gypsum-based unfired bricks.
[0029] The methods and process parameters of the remaining steps of this comparative example are the same as those of Example 3.
[0030] Comparative Example 2 This comparative example provides a method for preparing titanium gypsum-based unfired bricks. The difference from Example 3 is that 3250 g of titanium gypsum particles are replaced by a mixture of equal masses of alumina fiber powder and titanium gypsum particles, that is, 650 g of alumina fiber and 2600 g of titanium gypsum particles are mixed, and the mixed mixture is used to prepare titanium gypsum-based unfired bricks.
[0031] The methods and process parameters of the remaining steps of this comparative example are the same as those of Example 3.
[0032] Comparative Example 3 This comparative example provides a method for preparing titanium gypsum-based unfired bricks. The difference from Example 3 is that 3250 g of titanium gypsum particles are replaced by a mixture of equal mass of glass fiber powder and titanium gypsum particles, that is, 650 g of glass fiber and 2600 g of titanium gypsum particles are mixed, and the mixed mixture is used to prepare titanium gypsum-based unfired bricks.
[0033] The methods and process parameters of the remaining steps of this comparative example are the same as those of Example 3.
[0034] The compressive strength, softening coefficient and water absorption rate of the titanium gypsum-based unfired bricks prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were tested. The softening coefficient was determined with reference to JC_T 698-2010; the compressive strength and water absorption rate were determined with reference to TZJGFTR001-2022 titanium gypsum unfired brick product quality standard, and the results are shown in Table 1: Table 1 Performance test data of titanium gypsum-based unfired bricks prepared in Example 1 to Example 6 and Comparative Example 1 to Comparative Example 3 As can be seen from the above table, the titanium gypsum-based unfired bricks prepared in Examples 5 and 6 using titanium gypsum particles modified by composite fiber powder blending as the main raw materials have further improved properties such as compressive strength, water absorption rate and softening coefficient, and are also significantly better than Comparative Examples 1 to 3 in which alumina fiber powder, glass fiber powder and titanium gypsum particles are simply mixed, or alumina fiber powder, glass fiber powder and titanium gypsum particles are mixed separately.
[0035] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention will be obvious to those skilled in the art.
[0036] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the examples shown and described herein.
Claims
1. A titanium gypsum-based unfired brick, characterized in that: include: In terms of mass percentage, the titanium gypsum particles are 65.0-85.0%, the cement is 5.0-25.0%, the sand and gravel aggregate is 0-30.0%, the slag powder is 0-15%, and the calcium carbide slag is 0-3%.
2. The titanium gypsum-based unfired brick according to claim 1, characterized in that: The cement is ordinary Portland cement.
3. The titanium gypsum-based unfired brick according to claim 1, characterized in that: The cement is 42.5R ordinary silicate; The slag powder is S95 grade slag powder; The carbide slag is mainly composed of calcium hydroxide, and the content of calcium hydroxide is greater than 90%.
4. The titanium gypsum-based unfired brick according to claim 1, characterized in that: The invention also comprises 0.05% to 0.5% by mass of a curing agent and 0.05% to 0.5% by mass of a waterproofing agent.
5. The titanium gypsum-based unfired brick according to claim 1, characterized in that: The titanium gypsum particles are filtered through a plate and frame filter press to obtain a titanium gypsum filter cake, and then the titanium gypsum filter cake is hammer-crushed and dispersed to prepare the titanium gypsum filter cake.
6. The titanium gypsum-based unfired brick according to claim 4, characterized in that: The curing agent is a high molecular polymer, including one or more of polyacrylamide, polyvinyl acetate, polyurethane, polyvinyl alcohol, aniline formaldehyde resin, phenolic resin, furan resin, polyamide resin, and polyester resin.
7. The titanium gypsum-based unfired brick according to claim 4, characterized in that: The waterproofing agent is a silicone waterproofing agent.
8. A method for preparing a titanium gypsum-based unfired brick according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, mixing titanium gypsum particles, cement, sand and gravel aggregate, slag powder and carbide slag to obtain a mixture; Step 2: Add the curing agent and waterproofing agent into water and stir to obtain a mixed solution; Step 3: After the mixture and the mixed liquid are stirred and mixed evenly, they are placed in a mold and molded by a static brick-making machine through bidirectional pressing to obtain a brick blank; after curing the brick blank for 7 to 28 days, titanium gypsum-based unfired bricks can be obtained.
9. The method for preparing titanium gypsum-based unfired bricks according to claim 8, characterized in that: In the step 2, the amount of water used is 10% to 30% of the mass of the mixed material.
10. The method for preparing titanium gypsum-based unfired bricks according to claim 8, characterized in that: The prepared titanium gypsum unfired brick is tested according to GB / T17431-1998, and its compressive strength is between 5.00 and 30.00 MPa, its water absorption rate is less than 10%, and its softening coefficient is above 0.8.
Citation Information
Patent Citations
Moistureproof titanium gypsum hollow building block and preparation method thereof
CN102701698A
A titanium gypsum non-fired brick and its preparation process
CN115196934B
Cited By
Comprehensive recovery method of lithium slag
CN120714773A